UV-induced reaction kinetics in dilinoleoylphosphatidylcholine monolayers with incorporated photosensitizers - Marković Dejan (Journal of the Serbian Chemical Society, 2006)
Mixed insoluble monolayers (Langmuir films) of 1,2-di-O-linoleoyl-3-sn-phosphatidylcholine (1,2-DLPC) and incorporated benzophenone-type photosensitizers at an air-water interface were exposed to prolonged UV-irradiation. The irradiation was initiated at a particular fixed molecular packing value. Changes of the surface pressure during the UV-induced photolysis of the sensitizers were plotted against the irradiation time and the results were interpreted in terms of the molecular lipid/sensitizer ratios inside the monolayers.